Oxidative stress in the brain–lung crosstalk: cellular and molecular perspectives - Kong, Jianda; Fan, Rao; Zhang, Yuanqi; Jia, Zixuan; Zhang, Jing; Pan, Huixin; Wang, Qinglu (Frontiers in Aging Neuroscience, 2024)
Oxidative stress is caused by an imbalance between the production of reactive oxygen species (ROS) and the body’s ability to counteract their harmful effects, playing a key role in the pathogenesis of brain and lung-related diseases. This review comprehensively examines the intricate mechanisms by which oxidative stress influences cellular and molecular pathways, contributing to neurodegenerative, cardiovascular, and respiratory disorders. Emphasizing the detrimental effects on both brain and lung health, we discuss innovative diagnostic biomarkers, such as 8-hydroxy-2′-deoxyguanosine (8-OHdG), and the potential of antioxidant therapies. For these topics, we provide insights into future research directions in the field of oxidative stress treatment, including the development of personalized treatment approaches, the discovery and validation of novel biomarkers, and the development of new drug delivery systems. This review not only provides a new perspective on understanding the role of oxidative stress in brain and lung-related diseases but also offers new insights for future clinical treatments.